Teaching Cultural Competency through Global Health Education at Weill Cornell Medicine - Katharine-Grace Norris; Caitlin Noonan; Roger Ying; Claire T. Kenney; Jennifer Huang; Brienne Lubor; Rohini Kopparam; Elena Beideck; Priyanka Patel; Madelon L. Finkel (University Library System, University of Pittsburgh, 2020)
Background: Educating medical students to better understand the complexities of cultural competence, the social determinants and environmental determinants of health that are important and integral components of the medical school curriculum. Methods: In 2014, Weill Cornell Medicine (WCM) implemented a new curriculum, the adoption of which provided the means to enhance an existing global health program, informally introduced in 2009, and to address the issues of cultural competency. In this article, we share WCM's experience in building and expanding its global health curriculum. Results: A hallmark of our program is the successful collaboration between students and faculty to create a multi-disciplinary global health program that incorporates electives, clinical field placement, and collaborative research. Conclusion: Key lessons learned through our experience include the necessity for strong faculty-student collaboration, full support from the administration, and building global partnerships. Our example could be a useful guide for other medical schools seeking to establish a global health education curriculum.